Postcolonialism in Conflict - Tomczok, Marta (Porównania, 2022)
In this article, I analyze the concept of postcolonialism in conflict, proposed in the work entitled Polish Post-Colonial Literature. From Sarmatism to Post-Accession Migration (2020) by Dirk Uffelmann. Referring to the most important works of Polish researchers (Hanna Gosk, Dorota Kołodziejczyk, Magorzata Zduniak-Wiktorowicz, Ryszard Nycz), I try to show the assumptions of the German Slavicist, as well as understand the position that this work wants to take among other researchers of the postdependence of Polish culture. To this end, I follow the historical and literary order adopted by Uffelmann in the book, I also try to describe its individual parts. I pay particular attention to the concepts of self-orientalization, autoindianization and auto-proletarianization, through which the author presents the literature of the 19th, 20th and 21st centuries (including Henryk Sienkiewicz or postaccession migrants) in the victim-colonizer dichotomy. The traps of this dichotomy and the way of avoiding or tightening it in the academic discourse of Polish researchers of postdependence are discussed in the last part of the article.